A comparison of various minimally invasive techniques for the removal of dental fluorosis stains in children - Aarushi Gupta; Renuka Dhingra; Payal Chaudhuri; Anil Gupta (Wolters Kluwer Medknow Publications, 2017)
Context: Dental fluorosis is caused by successive exposure to high concentrations of fluoride during tooth development leading to enamel with lower mineral content and increased porosity. Aims: The aim of the study was to evaluate and compare the effectiveness of minimally invasive techniques for the removal of dental fluorosis stains in children in vivo. Design: Ninety children in the age group of 10-17 years were selected. Materials and Methods: The study sample was equally and randomly divided into three groups; Group 1: In-office bleaching with 35% hydrogen peroxide (HP) activated by light-emitting diode (LED) bleaching unit (35% HP), Group 2: Enamel microabrasion (EM) followed by in-office bleaching with 44% carbamide peroxide gel (EM), Group 3: In-office bleaching with 5% sodium hypochlorite (5% NaOCl). Statistical analysis was done using one-way ANOVA test. Results: Bleaching with 35% HP activated by LED bleaching unit and EM followed by bleaching with 44% carbamide peroxide were equally effective for the removal of dental fluorosis stains in children in vivo. However, bleaching with 5% NaOCl could not completely remove moderate to severe stains. It was effective in removing only mild stains. Bleaching and microabrasion procedures caused slight decrease in tooth sensitivity readings by electric pulp vitality tester which continued to increase over time. However, none of the patients reported sensitivity in their teeth at any point of time. Patients were highly satisfied with the treatment outcome postoperatively but reported slight relapse of color in the three groups. Conclusions: Bleaching and microabrasion techniques can consider as an interesting alternatives to conventional operative treatment options.